2012
DOI: 10.1159/000336903
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Open-Angle Glaucoma Measured by Spectral-Domain Scanning Laser Ophthalmoscopy/Optical Coherence Tomography

Abstract: Aims: To measure macular choroidal thickness in healthy and glaucomatous eyes using spectral-domain scanning laser ophthalmoscopy/optical coherence tomography. Methods: Choroidal thickness was measured in 21 healthy eyes and 16 glaucomatous eyes. Choroidal thickness was measured under the fovea and at 500-µm intervals from the foveal center to 4 mm in the nasal and temporal directions. Vessels were counted in a macular area of 8,000 µm2. Only choroidal vessels with a horizontal diameter of at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…18 The authors suggested that the finding of their study may reflect a lack of association between glaucoma and ChT. 20 In contrast with the results of the study by Mwanza and colleagues, the study by Cennamo et al 23 In the present study, the mean IOP after water ingestion at 30-and 60-minute time-points were higher when compared with their respective baseline levels in both XFS subjects and controls. This finding is also in agreement with the findings of Mansouri et al, 7 in which IOP elevation was observed after water ingestion in healthy volunteers.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…18 The authors suggested that the finding of their study may reflect a lack of association between glaucoma and ChT. 20 In contrast with the results of the study by Mwanza and colleagues, the study by Cennamo et al 23 In the present study, the mean IOP after water ingestion at 30-and 60-minute time-points were higher when compared with their respective baseline levels in both XFS subjects and controls. This finding is also in agreement with the findings of Mansouri et al, 7 in which IOP elevation was observed after water ingestion in healthy volunteers.…”
Section: Discussioncontrasting
confidence: 83%
“…In terms of the relationship between glaucoma and ChT, there are conflicting results in the literature. [20][21][22][23] In the study by Mwanza and colleagues, in which ChT was evaluated using EDI-OCT, no difference in ChT between normal subjects, normal-tension glaucoma, and patients with POAG could be demonstrated. 18 The authors suggested that the finding of their study may reflect a lack of association between glaucoma and ChT.…”
Section: Discussionmentioning
confidence: 96%
“…The difference in thickness of at least 63 lm as a statistically significant difference, as recently reported by Cennamo et al, 26 was used to determine whether the choroid was thinner or thicker in either eye of each patient or whether it was similar in both eyes (equal to or less than 62 lm). Choroidal thicknesses of eyes with severe glaucoma were compared to those of fellow eyes using multivariate general linear model after adjusting for axial length and IOP.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the included studies used Heidelberg Spectralis EDI-OCT (Heidelberg Engineering, Heidelberg, Germany) to obtain choroidal thickness data. In addition, there were 2 studies using Cirrus HD-OCT (Carl Zeiss Meditec, Dublin, CA), 42,46 1 study using RTVue-100 SD-OCT (Optovue Inc., Fremont, CA), 43 and 1 study using swept-source high-penetration OCT (SS-OCT) 30 which is a prototype introduced by Yasuno et al 47 There were 15 studies containing choroidal thickness data under the fovea 25,26,[28][29][30][31]35,[38][39][40][41][42][43]45,46 and 10 articles reporting choroidal thickness data surrounding the ONH. 25,27,[32][33][34][36][37][38]42,44 One of the 15 studies on subfoveal choroidal thickness (SFCT) included 3 study groups, so we separately compared the normal control group with the other 2 OAG patient groups (POAG group and NTG group).…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…For these reasons, we chose the SFCT data and the average PCT to be pooled. 25,26,[28][29][30][31]35,[38][39][40][41][42][43]45,46 between OAG patients and controls found significant heterogeneity (I 2 = 85.1%) across the articles, so the data were pooled through the random-effects model. The meta-analysis of these data showed that the SFCT in OAG patients was not significantly thinner compared with that in controls (WMD = À7.94; 95% confidence interval, À 26.01 to 10.13; P = 0.389, Fig.…”
Section: Meta-analysis Of Choroidal Thicknessmentioning
confidence: 99%